Evidence of governance arbitrage by private equity sponsors. (17th September 2018) - Schofield, Guy
Abstract: The motivation for private equity bids is not well understood, partly due to the private nature of their activity. This research contributes to understanding the merits of current‐day private equity by examining whether ineffective governance of target public corporations contributes to the role that private equity fulfils. I examine the characteristics of large public target firms that receive a private equity bid to investigate the evidence that private equity is motivated to address ineffective governance. I find evidence the private equity is motivated by what is referred to as governance arbitrage and that this role is heightened when there are constraints such as the imposition of uniform governance practices within public corporations.